The potential role of cell phones in dissemination of bacteria in a healthcare sett - Mateusz P. Kister; Katarzyna Borowska; Barbara Jodłowska-Jędrych; Karolina A. Kister; Bartłomiej Drop (Our Dermatology Online, 2016)
The mobile phone is an indispensible accessory, both from a social and a professional point of view, which is being used in a variety of environments, including those with high bacteria levels. Medical personnel, patients or even people simply passing by the healthcare facilities, having and using their mobile phones are likely to transmit bacteria, thus it might be suspected that mobile phones are to some extent a link in the cross-contamination. The purpose of this work was to collect information concerning the potential role of cell phones in a dissemination of bacteria based on available research data.